Investigating the Effect of Flipped Classroom on the Anxiety of Iranian English Language Learners - Faryadi, Mansour; Aliakbari, Mohammad; Seyedrezaei , Seyed Hasan; Mazandarani, Omid (Assessment and Practice in Educational Sciences, 2026)
The objective of this study was to examine the effect of flipped classroom instruction on reducing speaking anxiety among Iranian learners of English as a foreign language. This study adopted a quantitative mono-method research design using a cross-sectional online survey. The participants consisted of 105 Iranian adult EFL learners aged 18 years and above. Data were collected using a validated questionnaire measuring flipped classroom instructional components, including course content, facilities, lecturer and faculty support, concern for students, social activities, assessment practices, and instructional media, as well as learners’ speaking anxiety. Content validity of the instrument was confirmed through expert evaluation using content validity ratio and content validity index procedures, and reliability was established through Cronbach’s alpha coefficients exceeding acceptable thresholds. The collected data were analyzed using SPSS software. Descriptive statistics were computed to examine the distributional properties of the variables, and inferential analyses were conducted through multiple regression modeling and analysis of variance. Normality assumptions were verified using the Kolmogorov–Smirnov test, and model adequacy was assessed through R, R², F-statistics, Durbin–Watson, and multicollinearity diagnostics. The regression model revealed a strong and statistically significant relationship between flipped classroom instruction and speaking anxiety (R = 0.915, R² = 0.837, F = 84.09, p < .001). All flipped instructional components demonstrated significant predictive effects on reducing speaking anxiety, with social activities and instructional media exhibiting the strongest standardized coefficients. The results indicate that approximately 84% of the variance in learners’ anxiety levels was explained by the flipped classroom model. The findings provide robust empirical evidence that flipped classroom instruction significantly reduces speaking anxiety among Iranian EFL learners by fostering interactive, supportive, and learner-centered classroom environments.